Vessel wall magnetic resonance imaging in intracranial aneurysms: Principles and emerging clinical applications. Issue 2 (April 2020) - Santarosa, Corrado; Cord, Branden; Koo, Andrew; Bhogal, Pervinder; Malhotra, Ajay; Payabvash, Sam; Minja, Frank J; Matouk, Charles C
Intracranial high-resolution vessel wall magnetic resonance imaging is an imaging paradigm that complements conventional imaging modalities used in the evaluation of neurovascular pathology. This review focuses on the emerging utility of vessel wall magnetic resonance imaging in the characterization of intracranial aneurysms. We first discuss the technical principles of vessel wall magnetic resonance imaging highlighting methods to determine aneurysm wall enhancement and how to avoid common interpretive pitfalls. We then review its clinical application in the characterization of ruptured and unruptured intracranial aneurysms, in particular, the emergence of aneurysm wall enhancement as a biomarker of aneurysm instability. We offer our perspective from a high-volume neurovascular center where vessel wall magnetic resonance imaging is in routine clinical use.